SYSTEMATIC LITERATURE REVIEW: IDENTIFIKASI GAP DAN KELEMAHAN IMPLEMENTASI KEBIJAKAN PENDIDIKAN DI INDONESIA PERIODE 2015-2024 - Heriyadi; Rahmi, Indriati; Sulistiawan, Edi; Kusmiran, Ari Hardi; Sulistiyana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study systematically examines gaps and weaknesses in educational policy implementation in Indonesia during 2015-2024 through a systematic literature review approach. The complexity of Indonesia's educational system, encompassing geographical, socioeconomic, and cultural diversity, creates significant challenges in implementing strategic policies such as Curriculum 2013, PPDB zoning policy, Smart Indonesia Card program, and educational digitalization. The research methodology employs systematic analysis of ten selected empirical studies from various national and international academic databases with inclusion criteria of publications from 2015-2024. Research findings identify five primary dimensions of implementation weaknesses: (1) structural and infrastructure deficiencies with 80% of schools lacking adequate laboratory facilities; (2) inadequate human resource capacity where 65% of teachers do not understand new learning methodologies; (3) weak targeting and monitoring systems with 40% of assistance missing intended targets; (4) ineffective multi-level governance coordination; and (5) minimal policy adaptation to local contexts. Findings indicate that implementation weaknesses are systemic and multidimensional, requiring fundamental transformation in implementation approaches through infrastructure capacity strengthening, continuous professional development, data-based monitoring systems, integrated coordination, and adaptive decentralization to ensure achievement of Sustainable Development Goals in education and enhance national competitiveness.